Sieving rate-based polysiloxane crosslinking degree judgment method

The degree of crosslinking of polysiloxane is determined by the sieve rate method, which solves the problem of difficult to judge the crosslinking degree in the prior art, and achieves rapid and accurate crosslinking degree evaluation, which improves the performance and production efficiency of metal-based composite materials. .

CN119269347AActive Publication Date: 2025-01-07DALIAN JIAOTONG UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411421519.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-07
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The degree of crosslinking of existing polysiloxane crosslinked solids is difficult to judge, resulting in complex testing processes, high environmental requirements and difficult to popularize, affecting the yield and cost of ceramicized high-temperature sintering.

Method used

The siloxane crosslinking degree is determined by using a method based on the silencing rate. The silencing rate is calculated to determine the degree of crosslinking by mechanical mixing, standing crosslinking, grinding and passing through 200 to 250 mesh sieves. More than 80% is high, 60% to 80% is good, and less than 60% is poor.

Benefits of technology

It realizes rapid and accurate judgment of the degree of polysiloxane crosslinking, reduces testing costs and time, improves testing efficiency, and ensures the high strength and wear resistance of metal-based composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269347A_ABST
    Figure CN119269347A_ABST
Patent Text Reader

Abstract

The invention discloses a method for judging the crosslinking degree of polysiloxane based on a sieving rate, relates to the technical field of organosilicon polymers, and aims to solve the problems that the crosslinking degree of an existing polysiloxane crosslinking solid is difficult to judge, the test process is complex, the experimental environment requirement is high, and the method is difficult to popularize in actual production. Comprising the following steps: step 1, mixing polysiloxane and a crosslinking catalyst, carrying out standing crosslinking on the mixture of the polysiloxane and the catalyst at 40-60 DEG C for 2 days or more to obtain a polysiloxane cross-linked solid, and fully grinding the obtained polysiloxane cross-linked solid to obtain polysiloxane cross-linked solid powder; step 2, fully sieving the polysiloxane cross-linked solid powder through a 200-250-mesh sieve, calculating the sieving rate, and if the sieving rate exceeds 80%, indicating that the cross-linking degree of the polysiloxane cross-linked solid is relatively high; if the sieving rate is 60%-80%, the crosslinking degree of the polysiloxane crosslinking solid is good; if the sieving rate is lower than 60%, the crosslinking degree of the polysiloxane crosslinking solid is relatively poor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organosilicon polymers, and in particular to a method for judging the crosslinking degree of polysiloxane based on screening rate. Background Art

[0002] Ceramic particle reinforced metal matrix composites not only have the advantages of high hardness, good wear resistance and high temperature resistance of ceramic materials, but also have the characteristics of good toughness and high ductility of metal materials. Therefore, this material is an ideal material to meet the normal service of certain key core components under extreme environments such as high load and high temperature difference. High temperature ceramicization of organic-metal powder cross-linked mixture and its high pressure rolling technology are an ideal method for preparing ceramic particle reinforced metal matrix composites. The metal composite prepared by this method has excellent ceramic particle dispersion uniformity and can greatly improve the strength and wear resistance of the metal composite. The specific implementation process of this method is as follows: after the organic liquid (such as polysiloxane) and the metal powder are mixed in proportion, a cross-linking catalyst is added to cause a cross-linking reaction between the organic molecules wrapped around the metal particles, and the organic matter gradually changes from a liquid state to a solid state to form a solid organic-metal powder cross-linked mixture. The organic-metal powder cross-linked mixture is pyrolyzed at a certain temperature to convert the cross-linked organic matter into inorganic ceramic particles, and then the pyrolysis product is subjected to large plastic deformation treatment to achieve uniform dispersion of ceramic particles in the metal, thereby achieving ceramic reinforcement of the metal matrix. In summary, the core of this method is the cross-linking reaction of organic liquid under the action of catalyst. Only cross-linked organic molecules can be converted into ceramic particles during pyrolysis, while free organic molecules that are not fully cross-linked will be evaporated and removed during pyrolysis. Therefore, the degree of cross-linking of organic liquid is a key factor affecting the performance of metal matrix composites.

[0003] For polysiloxane liquid, after adding the crosslinking catalyst, the viscosity of the free-flowing liquid polysiloxane increases rapidly in a short time and eventually turns into a solid with dense pores, such as Figure 1 As shown. However, even if the polysiloxane has been cross-linked and formed a macroscopic solid, there are still large differences in the degree of cross-linking of the polysiloxane under different environmental conditions such as temperature, humidity, and placement time. The greater the degree of cross-linking of the polysiloxane, the more conducive it is to link more free polysiloxane molecules together, which is beneficial to reduce the loss of free polysiloxane molecules during the subsequent high-temperature pyrolysis of the cross-linked solid powder, thereby increasing the yield of the high-temperature pyrolysis product, ensuring that the metal-based composite material has good performance, and is conducive to the subsequent calculation of the content of the pyrolysis product and the control of the composition. Therefore, in actual production and application, it is hoped that the cross-linked solid can achieve a higher degree of cross-linking before high-temperature pyrolysis.

[0004] However, there is currently no clear method for determining the degree of crosslinking of the solid. Since the crosslinked solid formed after crosslinking of polysiloxane is a typical soft and brittle material, it is very easy to break when subjected to external force. Therefore, it is impossible to refer to the dynamic torsional vibration method in the resin curing determination method to measure the degree of crosslinking of the crosslinked solid. As a result, the yield of the sintered product is difficult to control and optimize during the high-temperature sintering of the polysiloxane crosslinked solid for ceramicization, resulting in low yield and high cost in actual production applications. Summary of the invention

[0005] The technical problems to be solved by the present invention are:

[0006] The degree of cross-linking of existing polysiloxane cross-linked solids is difficult to determine, and there are often problems such as complex testing processes, high requirements for experimental environments, and difficulty in popularization in actual production.

[0007] The present invention adopts the following technical solutions to solve the above technical problems:

[0008] The present invention provides a method for determining the crosslinking degree of polysiloxane based on screening rate, which is characterized by comprising the following steps:

[0009] Step 1: mechanically mixing polysiloxane and a cross-linking catalyst according to a cross-linking process to obtain a mixture of polysiloxane and a catalyst, and statically cross-linking the polysiloxane and the catalyst mixture at 40 to 60° C. for 2 days or more to obtain a polysiloxane cross-linked solid, and fully grinding the obtained polysiloxane cross-linked solid to obtain a polysiloxane cross-linked solid powder;

[0010] Step 2: Fully pass the polysiloxane cross-linked solid powder through a 200-250 mesh sieve, and calculate the sieving rate. If the sieving rate exceeds 80%, it means that the cross-linking degree of the polysiloxane cross-linked solid is high; if the sieving rate is 60%-80%, it means that the cross-linking degree of the polysiloxane cross-linked solid is good; if the sieving rate is less than 60%, it means that the cross-linking degree of the polysiloxane cross-linked solid is poor.

[0011] Furthermore, in step 1, a cross-linking catalyst is added at a mass fraction of 5 to 8%.

[0012] Furthermore, the obtained polysiloxane cross-linked solid is fully ground in step 1, specifically: the polysiloxane cross-linked solid is ground until the number of particles with a particle size of less than 70 μm accounts for no less than 80%.

[0013] Furthermore, in step 1, the obtained polysiloxane solid is fully ground using a ball mill, the ball milling speed is 200-600 r / min, and the ball milling time is not less than 5 min.

[0014] Furthermore, the viscosity of the polysiloxane at 20° C. is 15 to 40 mPa·s.

[0015] Furthermore, the polysiloxane in step 1 is one of polymethyl hydrogen siloxane, polyvinyl siloxane, polycarbosiloxane, polymethyl silsesquioxane or polyvinyl siloxane.

[0016] Furthermore, the catalyst in step 1 is one of triethylenediamine, a platinum-based complex or a vinyl polymer.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention provides a method for determining the crosslinking degree of polysiloxane based on screening rate, which can realize convenient and rapid determination of the crosslinking degree of polysiloxane and has the following advantages:

[0019] a) The method of the present invention fills the gap in the field of rapid estimation and judgment of the cross-linking degree of polysiloxane, can be used for a large number of explorations and optimizations of cross-linking processes, and provides technical support for stably achieving a high cross-linking degree of polysiloxane.

[0020] b) The method of the present invention requires less cross-linked solids in the testing process, which can reduce the testing cost, is easy to perform, and can quickly determine the degree of cross-linking in a short time, thereby improving the testing efficiency.

[0021] c) The method of the present invention utilizes the difference in screening characteristics of cross-linked solid powders at different cross-linking degrees to judge the degree of cross-linking. The judgment result is accurate and reliable with high precision. The method of the present invention can be used to prepare SiOC micro-ceramics, laying a foundation for further preparing metal-based composite materials with high strength, high wear resistance and high toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a morphology diagram of a cross-linked solid of polysiloxane in the background technology of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of a polysiloxane solid with a high degree of crosslinking after grinding in an embodiment of the present invention;

[0024] Figure 3 is a scanning electron microscope image of a polysiloxane solid with a low cross-linking degree after grinding in an embodiment of the present invention;

[0025] Figure 4 is a graph showing the relationship between the degree of crosslinking and the screening rate in an embodiment of the present invention;

[0026] Figure 5 This is a scanning electron microscope image of a polysiloxane solid powder with a high degree of cross-linking in an embodiment of the present invention;

[0027] Figure 6This is a scanning electron microscope image of a polysiloxane solid powder with a low degree of crosslinking in an embodiment of the present invention;

[0028] Figure 7 The powder particle size statistics in the embodiment of the present invention are Figure 1 ;

[0029] Figure 8 The powder particle size statistics in the embodiment of the present invention are Figure 2 ;

[0030] Fig. 9 The powder particle size statistics in the embodiment of the present invention are Figure 3 ;

[0031] Fig.10 The powder particle size statistics in the embodiment of the present invention are Figure 4 ;

[0032] Fig.11 The powder particle size statistics in the embodiment of the present invention are Figure 5 . DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0035] Example 1

[0036] Step 1-1: Weigh 19 g of polymethylhydrogensiloxane and 1 g of catalyst triethylenediamine respectively;

[0037] Step 1-2: Put 19 g of polymethylhydrogensiloxane into a beaker, and heat the beaker in a heat-collecting constant temperature heating magnetic stirrer preheated to 50° C.;

[0038] Step 1-3: Add 1 g of the catalyst weighed into a beaker containing polysiloxane, turn on the magnetic stirring function of the heat-collecting constant temperature heating magnetic stirrer, set the speed to 20 r / s, and mechanically mix the polysiloxane and the catalyst until the catalyst is fully dissolved to obtain a mixture of polysiloxane and the catalyst;

[0039] Step 1-4: placing the polysiloxane and catalyst mixture in a constant temperature and humidity test chamber preheated to 50° C. and 40% RH, and allowing to crosslink for 5 days to obtain a polysiloxane crosslinked solid;

[0040] Step 1-5: Take a solid sample of the polysiloxane cross-linked product and put it into a small ball mill, set the rotation speed to 500 r / min, the ball milling time to 5 min, and then start the ball mill to grind the cross-linked sample.

[0041] Step 1-6: Take out a small amount of ground solid powder and place it under an ultra-depth-of-field optical microscope for observation. At a magnification of 500 times, observe the microscopic morphology of individual powder particles, and measure and count the particle size of individual powder particles in the current observation area.

[0042] Step 1-7: Move the observation area position, and measure and count the particle size of individual powder particles in the current observation area again. The number of areas used for observation is not less than three and they do not overlap with each other.

[0043] Step 1-8: Calculate and analyze the statistical particle size data to obtain the particle size distribution curve, such as Figure 7 shown.

[0044] Step 1-9: From the particle size distribution curve, it can be seen that the number of powder particles with a particle size of less than or equal to 70 μm accounts for about 89.13%. If it is greater than 80%, proceed to the next step, otherwise continue grinding until the number of powder particles with a particle size of less than or equal to 70 μm accounts for no less than 80%.

[0045] Step 1-10: The mass of all the ground polysiloxane solid powder is weighed using an electronic balance with an accuracy of not less than 0.1 mg to obtain a mass of 11.309 g, which is recorded as m1.

[0046] Step 2-1: Pour all the weighed polysiloxane solid powder into a small vibrating sieve machine, select the sieve aperture size as 200 mesh, set the vibrating time to 3 minutes, the vibrating frequency to 1400 times / minute, the amplitude to 2 mm, and then start the vibrating sieve machine.

[0047] Step 2-2: The solid powder passing through the sieve is collected and retained.

[0048] Step 2-3: Collect the larger solid powder that does not pass through the sieve and pour it into a ball mill or mortar for further grinding and refinement.

[0049] Step 2-4: Pour the re-ground solid powder into the cleaned small vibrating sieve machine and sieve it again according to the parameters in step 2-1.

[0050] Step 2-5: Repeat grinding and sieving until the amount of powder passing through the sieve no longer increases, and mix the polysiloxane solid powders sifted each time.

[0051] Step 2-6: Use an electronic balance to weigh the mass of the solid powder that passes through the sieve, which is 10.430 g, and record it as m2.

[0052] Step 2-7: Calculate the screening rate:

[0053] η=(m2 / m1)*100% (1)

[0054] Step 2-8: Calculate the screening rate to 92.24%.

[0055] Step 2-9: Weigh 5 g of the sieved polysiloxane cross-linked product using an electronic balance with an accuracy of 0.1 mg, and record it as m3.

[0056] Step 2-10: Put the weighed cross-linked product into a corundum crucible, and put the crucible containing the cross-linked product into a tube furnace.

[0057] Step 2-11: introduce argon gas into the tubular furnace, set the heating rate to 5°C / min, set the maximum heating temperature to 1000°C, heat to 1000°C, keep warm for 2 hours, and cool with the furnace.

[0058] Step 2-12: After the tube furnace is cooled to room temperature, the cross-linked product after pyrolysis is taken out.

[0059] Step 2-13: Use an electronic balance with an accuracy of 0.1 mg to weigh the mass of the product obtained by pyrolysis to be 4.356 g and record it as m4.

[0060] Step 2-14: Use formula (2) to calculate the mass ratio θ of the polysiloxane cross-linked solid powder before and after pyrolysis:

[0061] The obtained value of θ is 87.12%.

[0062] The cross-linking reaction of polysiloxane forms a solid three-dimensional network structure, which is easy to enclose liquid uncross-linked polysiloxane linear molecules. The polysiloxane cross-linked product with a high degree of cross-linking has fewer residual uncross-linked polysiloxane linear molecules, so the liquid uncross-linked polysiloxane linear molecules enclosed in its network structure are fewer, and it completely shows the characteristics of a hard and brittle solid in macroscopic terms. The polysiloxane cross-linked product after grinding in this example has a high degree of dispersion, such as Figure 2 As shown in the figure, the fracture of the polysiloxane cross-linked solid is sharp, and cracks can be observed on its surface. Such cracks are usually seen on the surface of hard and brittle phases. Its solid powder is drier and easier to disperse, such as Figure 5As shown in the figure, it can pass through the sieve smoothly during the screening operation. On the contrary, the cross-linked polysiloxane with a low degree of cross-linking has more liquid non-cross-linked polysiloxane linear molecules in its network structure. Macroscopically, some of them appear to be in an intermediate state during the liquid-solid transition process, making them soft and elastic. After grinding, the dispersion of the cross-linked polysiloxane is low, as shown in the figure below. Figure 3 As shown in the figure, the fracture of the cross-linked polysiloxane solid is smooth, and the linear molecules of the liquid uncross-linked polysiloxane are sticky, which makes the surface of the polysiloxane particles also have sticky characteristics, which sticks the dispersed polysiloxane solid particles together, that is, it is easy to agglomerate and difficult to disperse. Its solid powder is softer and easier to agglomerate into large-sized flocculent particles, such as Figure 6 As shown, it is difficult to pass through the screen during the screening operation.

[0063] The solid cross-linked polysiloxane can be fully pyrolyzed at 1000°C, and the uncross-linked polysiloxane molecules will volatilize during the pyrolysis process. The higher the degree of cross-linking, the fewer the number of uncross-linked polysiloxane molecules, and the less mass loss. At the same time, there are also main bond breakage, side chain decomposition, and release of small molecule gases. The polysiloxane cross-linked product is converted into the final product SiOC, resulting in a loss of mass of the product after pyrolysis, but the amount of loss is less than that of the uncross-linked polysiloxane. Therefore, the degree of cross-linking is characterized by the mass ratio before and after pyrolysis of the solid powder of the polysiloxane cross-linked product. Therefore, in this embodiment, a high degree of cross-linking is defined as a θ value greater than or equal to 80%, a good degree of cross-linking is defined as a θ value in the range of 60% to 80%, and a poor degree of cross-linking is defined as a θ value less than or equal to 60%.

[0064] Example 2

[0065] Step 1-1: Weigh 19 g of polymethylhydrogensiloxane and 1 g of catalyst triethylenediamine respectively;

[0066] Step 1-2: Put 19 g of polymethylhydrogensiloxane into a beaker, and heat the beaker in a heat-collecting constant temperature heating magnetic stirrer preheated to 50° C.;

[0067] Step 1-3: Add 1 g of the catalyst to a beaker containing polysiloxane, turn on the magnetic stirring function of the heat-collecting constant temperature heating magnetic stirrer, set the speed to 20 r / s, and mechanically mix the polysiloxane and the catalyst until the catalyst is fully dissolved to obtain a mixture of polysiloxane and the catalyst.

[0068] Step 1-4: placing the polysiloxane and catalyst mixture in a constant temperature and humidity test chamber preheated to 50° C. and 40% RH, and allowing to crosslink for 2 days to obtain a polysiloxane crosslinked solid;

[0069] Step 1-5: Place the cross-linked polysiloxane solid sample into a small ball mill, set the speed to 500 r / min, the ball milling time to 5 min, then start the ball mill to grind the cross-linked sample, such as Figure 2 shown.

[0070] Step 1-6: Take out a small amount of solid powder after grinding and place it under an ultra-depth of field optical microscope for observation, such as Figure 5 As shown, at a magnification of 500 times, the microscopic morphology of a single powder particle is observed, and the particle size of a single powder particle in the current observation area is measured and counted.

[0071] Step 1-7: Move the observation area position, and measure and count the particle size of individual powder particles in the current observation area again. The number of areas used for observation is not less than three and they do not overlap with each other.

[0072] Step 1-8: Calculate and analyze the statistical particle size data to obtain the particle size distribution curve, such as Figure 8 shown.

[0073] Step 1-9: From the particle size distribution curve, it can be seen that the number of powder particles with a particle size of less than or equal to 70 μm accounts for about 91.30%. If it is greater than 80%, proceed to the next step.

[0074] Step 1-10: The mass of all the ground polysiloxane solid powder is weighed using an electronic balance with an accuracy of not less than 0.1 mg to obtain a mass of 11.186 g, which is recorded as m1.

[0075] Step 2-1: Pour all the weighed polysiloxane solid powder into a small vibrating sieve machine, select the sieve aperture size as 200 mesh, set the vibrating time to 3 minutes, set the vibrating frequency to 1400 times / minute, set the amplitude to 2 mm, and then start the vibrating sieve machine.

[0076] Step 2-2: The solid powder passing through the sieve is collected and retained.

[0077] Step 2-3: Collect the larger solid powder that does not pass through the sieve and pour it into a ball mill or mortar for further grinding and refinement.

[0078] Step 2-4: Pour the re-ground solid powder into the cleaned small vibrating sieve machine and sieve it again according to the parameters in step 2-1.

[0079] Step 2-5: Repeat grinding and sieving until the amount of powder passing through the sieve no longer increases, and mix the polysiloxane solid powders sifted through each sieve.

[0080] Step 2-6: Use an electronic balance to weigh the mass of the solid powder that passes through the sieve, which is 9.497 g and record it as m2.

[0081] Step 2-7: Calculate the screening rate:

[0082] η=(m2 / m1)*100% (1)

[0083] Step 2-8: Calculate the screening rate to 84.94%.

[0084] Step 2-9: Weigh 5 g of the sieved polysiloxane cross-linked product using an electronic balance with an accuracy of 0.1 mg, and record it as m3.

[0085] Step 2-10: Put the weighed cross-linked product into a corundum crucible, and put the crucible containing the cross-linked product into a tube furnace.

[0086] Step 2-11: introduce argon gas into the tubular furnace, set the heating rate to 5°C / min, set the maximum heating temperature to 1000°C, heat to 1000°C, keep warm for 2 hours, and cool with the furnace.

[0087] Step 2-12: After the tube furnace is cooled to room temperature, the cross-linked product after pyrolysis is taken out.

[0088] Step 2-13: Use an electronic balance with an accuracy of 0.1 mg to weigh the mass of the product obtained by pyrolysis to be 4.019 g and record it as m4.

[0089] Step 2-14: Use formula (2) to calculate the mass ratio θ of the cross-linked polysiloxane solid powder after pyrolysis to that before pyrolysis:

[0090] θ=(m4 / m3)*100% (2)

[0091] The calculated θ value is 80.38%, which shows that the cross-linking degree of the polysiloxane cross-linked solid with a screening rate of 84.94% is relatively high, and can be used for subsequent high-temperature pyrolysis to obtain a relatively high pyrolysis yield.

[0092] Example 3

[0093] Step 1-1: Weigh 19 g of polymethylhydrogensiloxane and 1 g of catalyst triethylenediamine respectively;

[0094] Step 1-2: Put 19 g of polymethylhydrogensiloxane into a beaker, and heat the beaker in a heat-collecting constant temperature heating magnetic stirrer preheated to 50° C.;

[0095] Step 1-3: Add 1 g of catalyst into a beaker containing polysiloxane, turn on the magnetic stirring function of the heat-collecting constant temperature heating magnetic stirrer, set the speed to 20 r / s, and mechanically mix the polysiloxane and the catalyst until the catalyst is fully dissolved to obtain a mixture of polysiloxane and the catalyst.

[0096] Step 1-4: placing the polysiloxane and catalyst mixture in a constant temperature and humidity test chamber preheated to 50° C. and 40% RH, and allowing to crosslink for 1 day to obtain a polysiloxane crosslinked solid;

[0097] Step 1-5: Place the polysiloxane cross-linked solid sample into a small ball mill, set the rotation speed to 500 r / min, the ball milling time to 5 min, and then start the ball mill to grind the cross-linked sample.

[0098] Step 1-6: Take out a small amount of ground solid powder and place it under an ultra-depth-of-field optical microscope for observation. At a magnification of 500 times, observe the microscopic morphology of individual powder particles, and measure and count the particle size of individual powder particles in the current observation area.

[0099] Step 1-7: Move the observation area position, and measure and count the particle size of individual powder particles in the current observation area again. The number of areas used for observation is not less than three and they do not overlap with each other.

[0100] Step 1-8: Calculate and analyze the statistical particle size data to obtain the particle size distribution curve, such as Fig. 9 shown.

[0101] Step 1-9: From the particle size distribution curve, it can be seen that the number of powder particles with a particle size of less than or equal to 70 μm accounts for about 84.78%. If it is greater than 80%, proceed to the next step.

[0102] Step 1-10: The mass of all the ground polysiloxane solid powder is weighed using an electronic balance with an accuracy of not less than 0.1 mg to obtain a mass of 11.439 g, which is recorded as m1.

[0103] Step 2-1: Pour all the weighed polysiloxane solid powder into a small vibrating sieve machine, select the sieve aperture size as 200 mesh, set the vibrating time to 3 minutes, the vibrating frequency to 1400 times / minute, the amplitude to 2 mm, and then start the vibrating sieve machine.

[0104] Step 2-2: The solid powder passing through the sieve is collected and retained.

[0105] Step 2-3: Collect the larger solid powder that does not pass through the sieve and pour it into a ball mill or mortar for further grinding and refinement.

[0106] Step 2-4: Pour the re-ground solid powder into the cleaned small vibrating sieve machine and sieve it again according to the parameters in step 2-1.

[0107] Step 2-5: Repeat grinding and sieving until the amount of powder passing through the sieve no longer increases, and mix the polysiloxane solid powders sifted through each sieve.

[0108] Step 2-6: Use an electronic balance to weigh the mass of the solid powder that passes through the sieve, which is 7.594 g and record it as m2.

[0109] Step 2-7: Calculate the screening rate:

[0110] η=(m2 / m1)*100% (1)

[0111] Step 2-8: Calculate the screening rate to 66.39%.

[0112] Step 2-9: Weigh 5 g of the sieved polysiloxane cross-linked product using an electronic balance with an accuracy of 0.1 mg, and record it as m3.

[0113] Step 2-10: Put the weighed cross-linked product into a corundum crucible, and put the crucible containing the cross-linked product into a tube furnace.

[0114] Step 2-11: introduce argon gas into the tubular furnace, set the heating rate to 5°C / min, set the maximum heating temperature to 1000°C, heat to 1000°C, keep warm for 2 hours, and cool with the furnace.

[0115] Step 2-12: After the tube furnace is cooled to room temperature, the cross-linked product after pyrolysis is taken out.

[0116] Step 2-13: Use an electronic balance with an accuracy of 0.1 mg to weigh the mass of the product obtained by pyrolysis, which is 3.576 g and is recorded as m4.

[0117] Step 2-14: Use formula (2) to calculate the mass ratio of the polysiloxane cross-linked solid powder before and after pyrolysis to characterize the cross-linking degree θ of the polysiloxane:

[0118] θ=(m4 / m3)*100% (2)

[0119] The calculated θ value is 71.52%, which shows that the polysiloxane cross-linked solid with a sieving rate of 66.39% has a lower degree of cross-linking.

[0120] Example 4

[0121] Step 1-1: Weigh 19 g of polymethylhydrogensiloxane and 1 g of catalyst triethylenediamine respectively;

[0122] Step 1-2: Put 19 g of polymethylhydrogensiloxane into a beaker, and heat the beaker in a heat-collecting constant temperature heating magnetic stirrer preheated to 50° C.;

[0123] Step 1-3: Add 1 g of the catalyst to a beaker containing polysiloxane, turn on the magnetic stirring function of the heat-collecting constant temperature heating magnetic stirrer, set the speed to 20 r / s, and mechanically mix the polysiloxane and the catalyst until the catalyst is fully dissolved to obtain a mixture of polysiloxane and the catalyst.

[0124] Step 1-4: placing the polysiloxane and catalyst mixture in a constant temperature and humidity test chamber preheated to 50° C. and 40% RH, and allowing to crosslink for 12 hours to obtain a polysiloxane crosslinked solid;

[0125] Step 1-5: Place the cross-linked polysiloxane solid sample into a small ball mill, set the speed to 500 r / min, the ball milling time to 5 min, then start the ball mill to grind the cross-linked sample, such as Figure 3 shown.

[0126] Step 1-6: Take out a small amount of solid powder after grinding and place it under an ultra-depth of field optical microscope for observation. At a magnification of 500 times, observe the microscopic morphology of a single powder particle, such as Figure 6 As shown, the particle size of each powder particle in the current observation area is measured and counted.

[0127] Step 1-7: Move the observation area position, and measure and count the particle size of individual powder particles in the current observation area again. The number of areas used for observation is not less than three and they do not overlap with each other.

[0128] Step 1-8: Calculate and analyze the statistical particle size data to obtain the particle size distribution curve, such as Fig.10 shown.

[0129] Step 1-9: From the particle size distribution curve, it can be seen that the number of powder particles with a particle size of less than or equal to 70 μm accounts for about 80.44%. If it is greater than 80%, proceed to the next step.

[0130] Step 1-10: The mass of all the ground polysiloxane solid powder is weighed using an electronic balance with an accuracy of not less than 0.1 mg to obtain a mass of 10.996 g, which is recorded as m1.

[0131] Step 2-1: Pour all the weighed polysiloxane solid powder into a small vibrating sieve machine, select the sieve aperture size as 200 mesh, set the vibrating time to 3 minutes, the vibrating frequency to 1400 times / minute, the amplitude to 2 mm, and then start the vibrating sieve machine.

[0132] Step 2-2: The solid powder passing through the sieve is collected and retained.

[0133] Step 2-3: Collect the larger solid powder that does not pass through the sieve and pour it into a ball mill or mortar for further grinding and refinement.

[0134] Step 2-4: Pour the re-ground solid powder into the cleaned small vibrating sieve machine and sieve it again according to the parameters in step 2-1.

[0135] Step 2-5: Repeat grinding and sieving until the amount of powder passing through the sieve no longer increases, and mix the polysiloxane solid powders sifted each time.

[0136] Step 2-6: Use an electronic balance to weigh the mass of the solid powder that passes through the sieve, which is 4.421 g, and record it as m2.

[0137] Step 2-7: Calculate the screening rate:

[0138] η=(m2 / m1)*100% (1)

[0139] Step 2-8: Calculate the screening rate to 40.21%.

[0140] Step 2-9: Weigh 5 g of the sieved polysiloxane cross-linked product using an electronic balance with an accuracy of 0.1 mg, and record it as m3.

[0141] Step 2-10: Put the weighed cross-linked product into a corundum crucible, and put the crucible containing the cross-linked product into a tube furnace.

[0142] Step 2-11: introduce argon gas into the tubular furnace, set the heating rate to 5°C / min, set the maximum heating temperature to 1000°C, heat to 1000°C, keep warm for 2 hours, and cool with the furnace.

[0143] Step 2-12: After the tube furnace is cooled to room temperature, the cross-linked product after pyrolysis is taken out.

[0144] Step 2-13: Use an electronic balance with an accuracy of 0.1 mg to weigh the mass of the product obtained by pyrolysis, which is 3.262 g and is recorded as m4.

[0145] Step 2-14: Use formula (2) to calculate the mass ratio of the polysiloxane cross-linked solid powder before and after pyrolysis to characterize the cross-linking degree θ of the polysiloxane:

[0146] θ=(m4 / m3)*100% (2)

[0147] The calculated θ value is 65.23%, which shows that the polysiloxane cross-linked solid with a sieving rate of 40.21% has a lower degree of cross-linking.

[0148] Example 5

[0149] In steps 1-4 of this embodiment, the static crosslinking time is 8 hours, and the rest is the same as in embodiment 2. The calculated sieving rate η is 6.42%, and the θ value is 40.12%, indicating that the polysiloxane crosslinked solid has a low degree of crosslinking.

[0150] Example 6

[0151] The static crosslinking time in steps 1-4 of this embodiment is 7 days, and the rest is the same as that of embodiment 2. The calculated sieving rate η is 94.98%, and the θ value is 90.16%, indicating that the polysiloxane crosslinked solid has a high degree of crosslinking.

[0152] Example 7

[0153] Step 1-1: Weigh 19 g of polymethylhydrogensiloxane and 1 g of catalyst triethylenediamine respectively;

[0154] Step 1-2: Put 19 g of polymethylhydrogensiloxane into a beaker, and heat the beaker in a heat-collecting constant temperature heating magnetic stirrer preheated to 40° C.;

[0155] Step 1-3: Add 1 g of the catalyst to a beaker containing polysiloxane, turn on the magnetic stirring function of the heat-collecting constant temperature heating magnetic stirrer, set the speed to 20 r / s, and mechanically mix the polysiloxane and the catalyst until the catalyst is fully dissolved to obtain a mixture of polysiloxane and the catalyst.

[0156] Step 1-4: placing the polysiloxane and catalyst mixture in a constant temperature and humidity test chamber preheated to 40° C. and 40% RH, and allowing to crosslink for 2 days to obtain a polysiloxane crosslinked solid;

[0157] Step 1-5: Place the polysiloxane cross-linked solid sample into a small ball mill, set the rotation speed to 500 r / min, the ball milling time to 5 min, and then start the ball mill to grind the cross-linked sample.

[0158] Step 1-6: Take out a small amount of ground solid powder and place it under an ultra-depth-of-field optical microscope for observation. At a magnification of 500 times, observe the microscopic morphology of individual powder particles, and measure and count the particle size of individual powder particles in the current observation area.

[0159] Step 1-7: Move the observation area position, and measure and count the particle size of individual powder particles in the current observation area again. The number of areas used for observation is not less than three and they do not overlap with each other.

[0160] Step 1-8: Calculate and analyze the statistical particle size data to obtain the particle size distribution curve, such as Fig.11 shown.

[0161] Step 1-9: According to the particle size distribution curve, it is calculated that the proportion of powder particles with a particle size of less than or equal to 70 μm reaches about 86.96%. If it is greater than 80%, proceed to the next step.

[0162] Step 1-10: The mass of all the ground polysiloxane solid powder is weighed using an electronic balance with an accuracy of not less than 0.1 mg to obtain a mass of 11.238 g, which is recorded as m1.

[0163] Step 2-1: Pour all the weighed polysiloxane solid powder into a small vibrating sieve machine, select the sieve aperture size as 200 mesh, set the vibrating time to 3 minutes, set the vibrating frequency to 1400 times / minute, set the amplitude to 2 mm, and then start the vibrating sieve machine.

[0164] Step 2-2: The solid powder passing through the sieve is collected and retained.

[0165] Step 2-3: Collect the larger solid powder that does not pass through the sieve and pour it into a ball mill or mortar for further grinding and refinement.

[0166] Step 2-4: Pour the re-ground solid powder into the cleaned small vibrating sieve machine and sieve it again according to the parameters in step 2-1.

[0167] Step 2-5: Mix the polysiloxane solid powders that have been sieved twice.

[0168] Step 2-6: Use an electronic balance to weigh the mass of the solid powder that passes through the sieve, which is 9.476 g and is recorded as m2.

[0169] Step 2-7: Calculate the screening rate:

[0170] η=(m2 / m1)*100% (1)

[0171] Step 2-8: Calculate the screening rate to 84.32%.

[0172] Step 2-9: Weigh 5 g of the sieved polysiloxane cross-linked product using an electronic balance with an accuracy of 0.1 mg, and record it as m3.

[0173] Step 2-10: Put the weighed cross-linked product into a corundum crucible, and put the crucible containing the cross-linked product into a tube furnace.

[0174] Step 2-11: introduce argon gas into the tubular furnace, set the heating rate to 5°C / min, set the maximum heating temperature to 1000°C, heat to 1000°C, keep warm for 2 hours, and cool with the furnace.

[0175] Step 2-12: After the tube furnace is cooled to room temperature, the cross-linked product after pyrolysis is taken out.

[0176] Step 2-13: Use an electronic balance with an accuracy of 0.1 mg to weigh the mass of the product obtained by pyrolysis to be 4.001 g and record it as m4.

[0177] Step 2-14: Use formula (2) to calculate the mass ratio θ of the polysiloxane cross-linked solid powder before and after pyrolysis:

[0178] θ=(m4 / m3)*100% (2)

[0179] The calculated θ value is 80.02%, and it can be seen that the polysiloxane cross-linked solid with a sieving rate η of 84.32% has a higher degree of cross-linking.

[0180] Example 8

[0181] In steps 1-2 and 1-4 of this embodiment, the temperature is set to 20° C., and the rest is the same as in embodiment 2. The calculated sieving rate η is 19.47%, and the θ value is 58.32%, indicating that the polysiloxane cross-linked solid has a lower cross-linking degree.

[0182] Example 9

[0183] In steps 1-2 and 1-4 of this embodiment, the temperature is set to 30° C., and the rest is the same as in embodiment 2. The calculated sieving rate η is 22.18%, and the θ value is 61.37%, indicating that the polysiloxane cross-linked solid has a lower degree of cross-linking.

[0184] Example 10

[0185] In steps 1-2 and 1-4 of this embodiment, the temperature is set to 60° C., and the rest is the same as in embodiment 2. The calculated sieving rate η is 86.15%, and the θ value is 85.28%, indicating that the polysiloxane cross-linked solid has a high degree of cross-linking.

[0186] Embodiment 11

[0187] In steps 1-2 and 1-4 of this embodiment, the temperature is set to 80°C, and the rest is the same as in Example 2. It was observed during the experiment that there was obvious white solid precipitation at the bottom of the container. This is because the cross-linking at a higher temperature accelerates the reaction rate of polysiloxane and the catalyst, and the liquid curing process is accelerated accordingly, but due to the fast curing process, part of the catalyst is not dissolved in the polysiloxane, but is precipitated at the bottom of the container, resulting in uneven polysiloxane solids.

[0188] Example 12

[0189] In step 2-1 of this embodiment, the mesh size is selected to be 250 mesh, and the rest is the same as in embodiment 2. The calculated screening rate η is 83.64%, and the θ value is 80.38%, indicating that the polysiloxane cross-linked solid has a high degree of cross-linking.

[0190] Example 13

[0191] In step 2-1 of this embodiment, the mesh size is selected to be 150 mesh, and the rest is the same as in embodiment 2. Since the mesh size of 100 mesh is 100 μm, the polysiloxane solid powder passes through the mesh all at once, and the screening rate is 100%, and this result is invalid.

[0192] Embodiment 14

[0193] In step 2-1 of this embodiment, the mesh size is selected to be 350 mesh, and the rest is the same as in Example 2. Since the mesh diameter of the 350 mesh mesh is small, steps 2-3, 2-4 and 2-5 need to be repeated multiple times, and during the repetition process, the polysiloxane powder will partially stick to the mesh or repeatedly pour out to cause mass loss, resulting in inaccurate calculation of the screening rate result.

[0194] Embodiment 15

[0195] In steps 1-5 of this embodiment, the rotation speed is set to 500 r / min, the ball milling time is 3 min, and the rest is the same as in Example 2. The calculated screening rate η is 53.69%, and the θ value is 80.38%. Due to the short grinding time, the polysiloxane solid particles are large, and the powder particles that do not meet the particle size of less than or equal to 70 μm account for more than 80%. In the subsequent screening process, ball milling and screening need to be repeated many times, which is prone to mass loss, resulting in inaccurate calculation of the screening rate.

[0196] Example 16

[0197] In steps 1-5 of this embodiment, the rotation speed is set to 500r / min, the ball milling time is 4min, and the rest is the same as in Example 2. The calculated screening rate η is 74.87%, and the θ value is 80.38%. When the ball milling time is 3min, the proportion of powder particles that do not meet the particle size of less than or equal to 70μm is greater than 80%. After grinding for 2 times, there are still a small amount of unscreened polysiloxane particles. The ball milling and screening process needs to be repeated for more than 3 times. The polysiloxane powder will easily have a large mass loss in the above process, resulting in inaccurate calculation of the screening rate result.

[0198] Embodiment 17

[0199] In steps 1-5 of this embodiment, the rotation speed is set to 500 r / min, the ball milling time is 7 min, and the rest is the same as in embodiment 2. The calculated screening rate η is 85.12%, and the θ value is 80.38%, which is similar to that in embodiment 2.

[0200] Embodiment 18

[0201] In step 1-1 of this embodiment, 19.8 g of polymethylhydrogensiloxane and 0.2 g of catalyst triethylenediamine (catalyst mass fraction is 1%) are weighed, and the rest is the same as in embodiment 2. The calculated sieving rate η is 16.01% and the θ value is 48.83%, indicating that the polysiloxane cross-linked solid has a low degree of cross-linking.

[0202] Embodiment 19

[0203] In step 1-1 of this embodiment, 19.6 g of polymethylhydrogensiloxane and 0.4 g of catalyst triethylenediamine (catalyst mass fraction is 2%) are weighed, and the rest is the same as in embodiment 2. The calculated sieving rate η is 18.33% and the θ value is 57.41%, indicating that the polysiloxane cross-linked solid has a low degree of cross-linking.

[0204] Embodiment 20

[0205] In step 1-1 of this embodiment, 18.4 g of polymethylhydrogensiloxane and 1.6 g of catalyst triethylenediamine (catalyst mass fraction is 8%) are weighed, and the rest is the same as in embodiment 2. The calculated sieving rate η is 85.46%, and the θ value is 81.13%, indicating that the polysiloxane cross-linked solid has a high degree of cross-linking.

[0206] Embodiment 21

[0207] In step 1-1 of this embodiment, 18 g of polymethylhydrogensiloxane and 2 g of catalyst triethylenediamine (catalyst mass fraction is 10%) are weighed, and the rest is the same as in Example 2. The calculated screening rate η is 86.23%, and the θ value is 82.16%. This indicates that the polysiloxane cross-linked solid has a high degree of cross-linking. However, it can be observed that the catalyst is in excess, and a white precipitate is formed at the bottom of the container.

[0208] The results of the pyrolysis yield-screening rate of the polysiloxane cross-linked solids obtained in Examples 1 to 11 and Examples 19 to 21 are as follows: Figure 4 As shown, when the pyrolysis yield reaches more than 70%, the screening rate increases significantly; when the screening rate is 80%, it can be considered that the polysiloxane has reached a high degree of crosslinking.

[0209] In the embodiment of the present invention, the polysiloxane may also be polyethylene siloxane, polycarbosiloxane, polymethylsilsesquioxane or polyethylene siloxane, and the viscosity of the polysiloxane at 20° C. is 15 to 40 mPa·s; the catalyst may also be a platinum-based complex or a vinyl polymer.

[0210] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for determining the degree of crosslinking of polysiloxane based on screening rate, characterized in that: The steps include: Step 1: mechanically mixing polysiloxane and a cross-linking catalyst according to a cross-linking process to obtain a mixture of polysiloxane and a catalyst, and statically cross-linking the polysiloxane and the catalyst mixture at 40 to 60° C. for 2 days or more to obtain a polysiloxane cross-linked solid, and fully grinding the obtained polysiloxane cross-linked solid to obtain a polysiloxane cross-linked solid powder; Step 2: Fully pass the polysiloxane cross-linked solid powder through a 200-250 mesh sieve, and calculate the sieving rate. If the sieving rate exceeds 80%, it means that the cross-linking degree of the polysiloxane cross-linked solid is high; if the sieving rate is 60%-80%, it means that the cross-linking degree of the polysiloxane cross-linked solid is good; if the sieving rate is less than 60%, it means that the cross-linking degree of the polysiloxane cross-linked solid is poor.

2. The method for determining the degree of crosslinking of polysiloxane based on screening rate according to claim 1, characterized in that: In step 1, a cross-linking catalyst is added at a mass fraction of 5 to 8%.

3. The method for determining the degree of crosslinking of polysiloxane based on screening rate according to claim 2, characterized in that: In step 1, the obtained polysiloxane cross-linked solid is fully ground, specifically: the polysiloxane cross-linked solid is ground until the number of particles with a particle size of less than 70 μm accounts for no less than 80%.

4. The method for determining the degree of crosslinking of polysiloxane based on screening rate according to claim 3, characterized in that: In step 1, the obtained polysiloxane solid is fully ground by a ball mill, the ball milling speed is 200-600 r / min, and the ball milling time is not less than 5 min.

5. The method for determining the degree of crosslinking of polysiloxane based on screening rate according to claim 1, characterized in that: The viscosity of the polysiloxane at 20° C. is 15 to 40 mPa·s.

6. The method for determining the degree of crosslinking of polysiloxane based on screening rate according to claim 1, characterized in that: The polysiloxane in step 1 is one of polymethyl hydrogen siloxane, polyvinyl siloxane, polycarbosiloxane, polymethyl silsesquioxane or polyvinyl siloxane.

7. The method for determining the degree of crosslinking of polysiloxane based on screening rate according to claim 1, characterized in that: The catalyst in step 1 is one of triethylenediamine, platinum-based complex or vinyl polymer.

Citation Information

Patent Citations

  • Ceramic raw material relative hardness detection method

    CN110146400A

  • Antibacterial hydrogel as well as preparation method and application thereof

    CN111363171A

  • Method for detecting residual quantity of cross-linking agent in sodium hyaluronate gel through image analysis

    CN116124754A

  • Water absorbing agent, water absorbing article and method for production of water absorbing agent

    SG134591A1

  • Process for ambient temperature grinding of soft polymers

    US4650126A